British Medical Association and the National Health Service Bill (1946)
1946 1946 1940s 8 pages not disqualified to serve as Members of Parliament, as members of local authorities and of any bodies concerned with the administration of the service, including regional boards, local hospital management committees and local executive councils. Industrial Medical Service 31. The exclusion from the scheme of the industrial medical service cannot be justified. The medical supervision of the worker at the factory should be linked with the supervision of his home environment as part of the same health service. Medical services in industry are of comparatively recent growth, and the opportunity should not be lost of integrating them with the main health service. Specialists in the Public Health Scrvice 32. While it is proposed to inaugurate selection committees for the appointment of specialists there is nothing in the Government's proposals to indicate that senior specialist officers in the Public Health service will be appointed otherwise than by local authorities. Medical Research 33. No new proposals are advanced for the expansion and development of medical research. The facilities and resources for medical research should be greatly increased. THE PROPOSALS AND THE PRINCIPLES 34. There are four of the profession's essential principles upon which the Government's proposals have a particular bearing: PRINCIPLE I The medical profession is, in the public interest, opposed to any form of service which leads directly or indirectly to the profession as a whole becoming full-time salaried servants of the State or local authorities. 35. The State will own all the hospitals in which consultants work, will appoint the governing bodies of hospitals and, through regional boards, will employ the consultant to work in or from its premises, the consultant being employed on a whole-time or part-time basis. Whether the hospital proposals will lead directly or indirectly to consultants and specialists becoming "full-time salaried servants of the State or local authorities" will largely depend on the composition and functions of the regional board, the local hospital management committee, the board of governors of the teaching hospital, and the committee of management of the individual hospital. 36. General practitioners will be in contact with local authorities, half professional and half lay. At the earliest possible moment they will conduct their public general practices in premises owned and administered by a local authority. They will be remunerated in substantial part by salary. New entrants to public general practice will be appointed by a mainly medical body set up by the Government and working under its general direction. The Government's proposals, in the Council's view, will lead to general practitioners "becoming full-time salaried servants of the State or local authorities." PRINCIPLE IV Doctors should, like other workers, be free to choose the form, place and type of work they prefer without governmental or other direction. 37. For the reasons set out in earlier paragraphs the Government's proposals are in conflict with this principle. PRINCIPLE V Every registered medical practitioner should be entitled as a right to participate in the public service. 38. The Government's proposals violate this principle. They contain no provision whereby a medical practitioner could claim the right to take part in the Service somewhere. The local executive councils will consider not only the need for a new practice or replacement, but also the suitability of the applicant. The applicant, although recognized and approved by the General Medical Council, might therefore find himself or herself excluded from the Service, either in particular areas or in every area. The present proposals, in the Association's view, should be replaced by provisions similar to Sections 35 (2) (b) and 36 of the National Health Insurance Act, 1936. Section 35 (2) (b) secures a right on the part of any medical practitioner who so desires of being included in the lists of medical practitioners who have agreed to attend and treat insured persons. Section 36 is as follows: "If the Minister, after such inquiry as may be prescribed, is satisfied that the continued inclusion in the list of any medical practitioner would be prejudicial to the efficiency of the medical service of the insured, the Minister may remove his name from the list." PRINCIPLE VII There should be adequate representation of the medical profession on all administrative bodies associated with the new service in order that doctors may make their contribution to the efficiency of the service. 39. The profession is promised medical representation on central advisory bodies, on regional boards and on local hospital management committees. Although it is promised a majority on the Central Health Services Council, the composition of regional boards and local hospital management committees, as of boards of governors of teaching hospitals, is not known. Even though local health authorities are to be required to establish public health committees, there is not to be a requirement to co-opt doctors and other non-members of the authority with experience of the health services. Thus the Government's present proposals present some points of conflict with this principle. 8 Printed in Great Britain by Fisher, Knight and Co., Ltd., The Gainsborough Press, St. Albans. 292/847/4/40